Contracting in Peer Networks - DEMARZO, PETER M.; KANIEL, RON (Journal of Finance, 2023)
ABSTRACT We consider multiagent multifirm contracting when agents benchmark their wages to those of their peers, using weights that vary within and across firms. When a single principal commits to a public contract, optimal contracts hedge relative wage risk without sacrificing efficiency. But compensation benchmarking undoes performance benchmarking, causing wages to load positively on peer output, and asymmetries in peer effects can be exploited to enhance profits. With multiple principals, a “rat race” emerges: agents are more productive, with effort that can exceed the first best, but higher wages reduce profits and undermine efficiency. Wage transparency and disclosure requirements exacerbate these effects.